Optimizing the design of high-fidelity simulation-based training activities using cognitive load theory – lessons learned from a real-life experience. Issue 2 (1st May 2017) - Sun, N Z; Anand, P A; Snell, L
Abstract: High-fidelity simulation-based training, such as those aimed at teaching the management of medical crises, constitutes a highly complex learning task. To be effective, its design must be guided by sound learning principles. Cognitive load theory is a well-developed framework and has been extensively used in other settings to improve instructional designs in medical education. We explain this theoretical framework and its relevance to the educational design of high-fidelity simulation using as an exemplar the McGill University internal medicine crisis resource management learning activity. We then conclude with a few practical suggestions on how to apply cognitive load theory in the design of high-fidelity simulation-based learning activities.